An approach to Lambe-Lambe Theatre as a scenic resonance device: (Intimate) heterotopias in the public space (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This study uses a process of qualitative interviews and research-creation to reflect during the Covid-19 pandemic, on the trade of the "lambista" in Lambe-Lambe Theatre concerning the making of immersive dramaturgies through scenic devices which contribute to an "experiences of resonance”. These elements altogether highlight the importance of "being present" in the creation of sensitive dramaturgies that give rise to "other spaces" and shape "intimate heterotopias" set in the disputed sociocultural territory of public space".
Keywords: intimate heterotopia; resonance; soundscape; Lambe-Lambe Theater; scenic device; object theater; street theater